Antibacterial activity of ethanolic extracts of marine algae from central coast of Peru - Magallanes, Claudio (2003)
Antibacterial activity of ethanolic extracts from 12 macroalgae were evaluated. Extracts were obtained according to the protocol of Vlachos et al. (1996). Extracts were tested against with 5 clinic strains and 6 no clinic strains of the genus Staphylococcus, Enterococcus, Pseudomonas, Escherichia, Salmonella, Aeromonas y Vibrio. Only Grateloupia doryphora, Ahnfeltiopsis durvillaei, Prionitis decipiens (Rhodophyta), Petalonia fascia (Phaeophyta) and Bryopsis plumosa (Chlorophyta) showed some antibacterial activity against the clinic strains Staphylococcus aureus ATCC 25923 and Enterococcus faecalis ATCC 29212 and the no clinic strain Staphylococcus aureus ATCC 6633. Ethanolic extract of B. plumosa presented the highest antibacterial activity against S. aureus strains. The extract of P. fascia showed the highest antibacterial activity against the three sensible strains.